Loss of methylation at the IFNG promoter and CNS‐1 is associated with the development of functional IFN‐γ memory in human CD4+ T lymphocytes. Issue 3 (11th March 2013) - Dong, Jun; Chang, Hyun‐Dong; Ivascu, Claudia; Qian, Yu; Rezai, Soheila; Okhrimenko, Anna; Cosmi, Lorenzo; Maggi, Laura; Eckhardt, Florian; Wu, Peihua; Sieper, Joachim; Alexander, Tobias; et al.
<x xml:space="preserve">Abstract</x> Cytokine memory for IFN‐γ production by effector/memory Th1 cells plays a key role in both protective and pathological immune responses. To understand the epigenetic mechanism determining the ontogeny of effector/memory Th1 cells characterized by stable effector functions, we identified a T‐cell‐specific methylation pattern at the IFNG promoter and CNS‐1 in ex vivo effector/memory Th1 cells, and investigated methylation dynamics of these regions during the development of effector/memory Th1 cells. During Th1 differentiation, demethylation occurred at both the promoter and CNS‐1 regions of IFNG as early as 16 h, and this process was independent of cell proliferation and DNA synthesis. Using an IFN‐γ capture assay, we found early IFN‐γ‐producing cells from 2‐day differentiating cultures acquired "permissive" levels of demethylation and developed into effector/memory Th1 cells undergoing progressive demethylation at the IFNG promoter and CNS‐1 when induced by IL‐12. Methylation levels of these regions in effector/memory Th1 cells of peripheral blood from rheumatoid arthritis patients correlated inversely with reduced frequencies of IFN‐γ‐producers, coincident with recruitment of effector/memory Th1 cells to the site of inflammation. Thus, after termination of TCR stimulation, IL‐12 signaling potentiates the stable functional IFN‐γ memory in effector/memory Th1 cells characterized by hypomethylation at the IFNG promoter and CNS‐1.